2021
DOI: 10.3390/metabo11050283
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics to Evaluate Progression of Necrotising Enterocolitis in Preterm Pigs

Abstract: Necrotising enterocolitis (NEC) is a microbiome-dependent gut disease in preterm infants in early life. Antibiotic treatment is a common intervention for NEC. How NEC lesions, with or without antibiotics, affect plasma metabolome was explored in this study. Formula-fed preterm pigs were used as a model for human NEC and treated with saline, parenteral or oral antibiotics (n = 15–17) for four days after delivery. Gut tissues were collected for evaluation of NEC-like lesions and plasma for metabolomic analysis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Exploring the relationship between multiple metabolites through multidimensional models is expected to provide a new means for the early prediction of related diseases, especially inflammatory bowel diseases, such as NEC, that are prone to occur after feeding premature infants (Fanos et al, 2013 ). We can even prevent the occurrence of NEC by interfering with metabolic pathways, as shown in animal models (Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the relationship between multiple metabolites through multidimensional models is expected to provide a new means for the early prediction of related diseases, especially inflammatory bowel diseases, such as NEC, that are prone to occur after feeding premature infants (Fanos et al, 2013 ). We can even prevent the occurrence of NEC by interfering with metabolic pathways, as shown in animal models (Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study comparing metabolites in urine samples of NEC preterm infants compared with a control group without NEC used proton nuclear magnetic resonance spectroscopy ( 1 H NMR) to find that late-onset NEC was associated with high lactate and decreased betaine, creatine, urea, myo-inositol, and N,N-dimethylglycine [61]. An animal study using preterm pigs as a model for NEC found higher serum levels of alanine, histidine, and myo-inositol and lower levels of 3-hydroxybutyric acid and isobutyric acid in animals with NEC [62]. Targeted metabolomics analysis of NEC and control fecal samples found that fecal fomic acid (fomate) was significantly increased at NEC onset and decreased with recovery [63].…”
Section: Gut Microbiome-brain Axis In Necrotizing Enterocolitismentioning
confidence: 99%